Stres i emocje studentów ostatniego roku Wydziału Lekarskiego. Znaczenie w zarządzaniu ochroną zdrowia - Turowska, Anna (Studia Edukacyjne, 2021)
The subjects were 134 final-year students of Warsaw Medical University, 1st Faculty of Medicine. The purpose of the study was to measure the dominant coping strategy, moderated by positive and negative emotions, which can be important in management. The variance analysis showed that activation of negative emotions resulted in a significant rise in emotion-oriented and avoidance-oriented coping. At the same time, the level of a task-oriented strategy decreased significantly, which seems to be very important in healthcare management.